A Study to Assess the Effectiveness of Deep Breathing Exercise on Blood Pressure and Heart Rate Among Hypertensive Patients in Selected Area of Kheda District - Vahora Anika; Patel Charmi; Ninama Hetal; Thakor Prachi; Momin Sakina; Damor Sarjana; Sachi Christia (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background of Study: Despite the significance of the problem with respect to overall health and its undesirablehealth consequences, high blood pressure still is not adequately controlled and far from being optimal. Anestimated 1.13 billion people worldwide have hypertension (WHO may 2019). In India incidence rate ofhypertension is 29.8% (WHO September 2018). In Gujarat incidence rate of hypertension is 27.1% (JNC-7). Quasi experimental research design (pre test post test research design), Quantitative research approachwas used to assess the effectiveness of deep breathing exercise on blood pressure and heart rate amonghypertensive patients in selected area of Kheda district. The collected data was tabulated and analyzed usingdescriptive and inferential statistics. Mean, and standard deviation was calculated by the obtained data inwhich mean score of blood pressure was 127.46 in pre test and 78.63 in post test and score of standarddeviation was 5.44 in pre test and 4.88 in post test. The mean score of heart rate was 86.2 in pre test and63.01 in post test and score of standard deviation was 3.86 in pre test and 2.59 in post test.